Synthesis of Monodisperse Colloidal ZnS Spheres by an Acid‐Free Two‐Step Approach. Issue 1 (5th October 2022) - Fang, Qianyao; Wei, Wuke; Wu, Chengcai; Su, Xin; Wu, Suli
Abstract: In this work, we demonstrate a new two‐step method for preparing monodisperse ZnS colloidal spheres. The method contains a hot‐injection step for making primary particles as seeds and a heating‐up step for aggregation growth of secondary colloidal spheres. Instead of the most commonly used thioacetamide in previous studies, thiourea (TU) was selected as the sulfur source. The temperature‐dependent thermal decomposition rate of TU makes the releasing of S 2− and nucleation of ZnS under proper kinetic control, meanwhile making the reaction a mild and acid‐free process. By separating the two steps and using a milder sulfur precursor, monodisperse ZnS colloidal spheres have been prepared. Their diameters can be delicately tuned in the range from 54 to 172 nm through simply changing the amount of Zn and S precursor. The optical properties of the obtained ZnS spheres were studied by extinction and PL measurements, and they exhibit size‐dependent optical behavior. Abstract : Monodisperse ZnS spheres have been prepared through a two‐step acid‐free method, which includes a hot‐injection step for making primary particles as seeds and a heating‐up step for aggregation growth of secondary colloidal spheres.